The Nura river saprobity degree determination by hydrobionts species composition - Abukenova, V.S.; Blyalova, Zh.Zh.; Blyalova, M.Zh. (KSU Publ., 2018)
The article contains information on the biological methods effectiveness for determining the saprobity degree of the water bodies by the microscopic representatives species composition of aquatic invertebrates. Aquatic invertebrates are very convenient for bioindication of the ecological state of aquatic ecosystems, as they make unnecessary (or often complement) the use of expensive and time-consuming physical and chemical methods of analysis of environmental parameters; reflect and record the rate of changes in the environment. Aquatic invertebrates, which are bioindicators of contamination, due to the impact of certain factors may show different degrees of intensity of the response in the form of dominance or partial or complete disappearance. In our opinion, there is a direct relationship between the intensity of the invertebrate response-indicators and water quality. It was used one of the most developed biological methods for evaluating water quality using indicator species of zooplankton and zoobenthos — the Pantle-Buck method in the Sladecek modification. The possibilities of studying the anatomical and morphological organization of microscopic fauna in the educational process are estimated. The hydrobionts species were determined, and a species list inhabiting this watercourse was also compiled. The indicator organisms have been identified, the organic contamination of the watercourse under investigation has been determined.
Нұра өзенінің гидробионттардың түрлік құрамы бойынша сапробтык дəрежесін анықтау
Определение степени сапробности реки Нуры по видовому составу гидробионтов
Keywords: degree of saprobity, saprobity index, zooplankton, zoobenthos, saprobiological analysis of the Pantle-Buck modified by Sladecek